Modulation of Yeast-Derived Volatile Aromas by Oleic Acid and Sterols - Fairbairn, S.; Silva Ferreira, A. C.; Bauer, F. F. (South African Journal of Enology and Viticulture, 2019)
Unsaturated fatty acids and sterols are essential constituents of the yeast plasma membrane. Recently, their contribution to modulating the production of yeast-derived volatile compounds has received significant attention. The objective of this study was to determine how sterol and lipid supplementation, including ergosterol, plant sterols or oleic acid, differentially influenced yeast growth as well as the production of fermentative aromas when added individually or in combinations. Oleic acid significantly altered the volatile profiles produced and lowered yeast growth. Generally, phytosterol (β-sitosterol) and ergosterol supplementation resulted in similar responses regarding the production of aromas, however, they differed in the magnitude of the response in the case of medium chain fatty acids and acetate esters synthesis. The combinations of sterols with oleic acid resulted in a response more closely associated with the oleic acid control treatment, showing lower levels of acetate ester production.